Factor flows between Australia and New Zealand - P. J. Lloyd (New Zealand Institute of Economic Research (NZIER), 2003)
Economic relations between Australia and New Zealand comprise trade in goods, services, labour and capital. Table 1 lists the dependence of Australia on New Zealand markets, and the dependence of New Zealand on Australian markets, in the simple sense of the magnitude of imports and exports of goods and services and factor flows with the other country. To make these flows comparable, each flow between Australia and New Zealand is expressed as a share of the total corresponding flow between the country and the Rest of the World. As is well known, this table shows that all of these shares are considerably higher for New Zealand than for Australia. That is, the New Zealand economy is more dependent on the Australian economy than the reverse. Looking at the comparisons within each column, we find that both the Australian and the New Zealand economies are more dependent on each other for factor supplies than they are for trade in goods and services. In particular, two flows really stand out as making Australia and New Zealand dependent upon each other. These are New Zealand supplies of labour to the Australian labour markets and trans-Tasman foreign direct investment. Consequently, while the usual focus on economic relations is on trade in goods and services, I shall focus on trade in factors.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Handelsregionalismus; Faktormobilität; Neuseeland; Australien